2021
DOI: 10.1080/10942912.2021.1898420
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of colour with the phytocompounds present in Cornus mas cultivars

Abstract: Cornelian cherry (Cornus mas L.) fruits are a well-known source of antioxidants and other biologically active compounds, and these compounds depend on maturity. Ripeness is recognized by means of a visual assay of the growing fruit. The study aimed to determine the relationship between the color of the tested cultivars of Cornus mas and their content of the predominant compounds (i.e., flavonoids, anthocyanins, vitamin C, carotenoids and chlorophyll). The studied deviation between cultivars is based on the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…According to the literature, the results regarding total polyphenols and total flavonoids are similar or slightly lower than those previously reported [ 37 , 38 ]. Similar to these findings, the total carotenoid content was comparable to or rather decreased than earlier published data [ 39 , 40 ]. However, it is generally accepted that cornelian cherry fruits contain a reduced quantity of carotenoid pigments.…”
Section: Discussionsupporting
confidence: 91%
“…According to the literature, the results regarding total polyphenols and total flavonoids are similar or slightly lower than those previously reported [ 37 , 38 ]. Similar to these findings, the total carotenoid content was comparable to or rather decreased than earlier published data [ 39 , 40 ]. However, it is generally accepted that cornelian cherry fruits contain a reduced quantity of carotenoid pigments.…”
Section: Discussionsupporting
confidence: 91%
“…There is a lot of information in the literature on phenolic acids, tannins, anthocyanins, and flavonoids in the content of CC fruits (Antolak et al, 2017; Cosmulescu et al, 2019; Dzydzan et al, 2019; Milenković‐Andjelković et al, 2015; Natić et al, 2019; Szczepaniak et al, 2019; Szczepaniak et al, 2021). However, there is little information on the polyphenol profile of CC products such as jam (Begic‐Akagic et al, 2013), marmalade (Savaş et al, 2020; Şengül et al, 2018), vinegar (Kawa‐Rygielska et al, 2018), and alcoholic beverages (Adamenko et al, 2018; Sokół‐Łętowska et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The amount and variety of polyphenolic compounds depend on the genotype, growing conditions, and maturity level of the fruit (Dinda et al, 2016; Szczepaniak et al, 2019), in addition to the production conditions of the product. Szczepaniak et al (2021) and Moldovan et al (2016) reported rutin and (+)‐catechin in raw CC fruits as 9.3–58.5 mg/100 g FW and 37.06 ± 1.73 mg/100 g FW, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very good way of extending the useful life of cornelian cherries is fruit freezing. Szczepaniak et al [89], comparing the color of frozen cornelian cherry fruits and that of thawed fruits, found that the distribution of anthocyanin pigments can affect fruit color luminosity due to the relationship between the degradation of anthocyanins and the development of yellow pigments. This can be observed as a decline in the value of parameter a*.…”
Section: Anthocyanins In Food Products Derived From Cornelian Cherrymentioning
confidence: 99%